Effect of Drought Stress in Various Enzymes of Pennisetum glaucum - Choudhary, Minakshi; Manjhi, Jayanand; Sinha, Anvesha (International Journal of Applied Sciences and Biotechnology, 2015)
Introduction: Pearl millet (Pennisetum glaucum) is an important cereal of traditional farming systems that has the natural ability to withstandvarious abiotic stresses such as drought, which is one of the most important manifestations of abiotic stress in plants. These plants havehowever evolved mechanisms that allow them to adapt and survive prolonged periods of water deficit at some level or form of plant structure,if not at the whole plant level. The hostile conditions augment the formation of reactive oxygen species (ROS) during physiological stresses inplants which are combated by various enzymatic and non-enzymatic mechanisms. The present study aims at examining the role of fourimportant enzymes namely Ascorbic peroxidase (APX), Peroxidase (POX), Catalase (CAT) and Superoxide Dismutase(SOD) expressed duringdrought stress in pearl millet (Pennisetum glaucum). Method: 12 and 22 days old seedlings of Pennisetum cultivar HHB-68 were subjectedto drought stress by treatment of 30% Polyethylene glycol for different time periods 30min (T1), 2hr (T2), 4hr (T3), 8hr (T4), 16hr (T5), 24hr(T6) and 48hr (T7) respectively, monitored by examining RWC of seedlings. The treatment seedlings were then used for investigating thelevels of enzymes activity in response to prolonged dehydration periods of 22 days. The enzyme activity of POX, APX, CAT and SOD wereassayed. Result: Enzymes expression was assayed for each treatment sets at both time intervals. Drought stress was observed to causeremarkable increase in POX, APX and SOD activity while incidence of CAT enzyme decreased with the increasing period of water deficit.Conclusion: Prolonged periods of water deficiency causes significant variations in expression of various enzymes in Pennisetum glaucum,known to be involved in ROS scavenging and drought stress management. The study provides a sturdy validation of the role of these enzymesas potent mechanisms undertaken by drought resistant plants for successful management of drought stress, which can be used for thedevelopment of more efficient and economic drought resistant cultivars. DOI: http://dx.doi.org/10.3126/ijasbt.v3i1.12278 Int J Appl Sci Biotechnol, Vol. 3(1): 134-138